Melacak Kemajuan Kognitif: Binaural Beats pada Gelombang Otak Alpha terhadap Working Memory - Frederica, Ruth; Putri, Angelina Anindya; Tunnufus, Azzah Dzakirah; Audiva, Alsyadiela; Pangestika, Odilia Melati; Pratiwi, Alfiantari Reika; Jatnika, Ratna (Kajian Psikologi dan Kesehatan Mental, 2024)
Purpose: This study aims to examine the effect of binaural beats in the alpha brain wave range on the working memory of Psychology students at Padjadjaran University, class of 2023. Alpha waves are associated with a relaxed yet alert state of consciousness. Research methodology: A quantitative experimental method was used with a one-group pretest-posttest design. Fifty participants were selected through stratified random sampling. The Brown-Peterson Task was employed to assess working memory, and data were analyzed using the Wilcoxon test. Results: The post-test scores (M = 4.38; SD = 1.50) were higher than the pre-test scores (M = 4.00; SD = 1.47), indicating an improvement in working memory after exposure to alpha binaural beats. Wilcoxon analysis confirmed a significant difference. Conclusions: Alpha wave binaural beats significantly improved the working memory of Psychology students at Unpad class of 2023. Limitations: The pretest-posttest method may have introduced familiarity bias. Future research should modify post-test content to minimize this effect and involve larger, more diverse samples to enhance generalizability. Contribution: This study contributes to students by considering techniques for improving their working memory abilities.